Lidocaine Prilocaine Cream versus LidocaineHCL Injection for Pain Relief during Second Degree of Perineal Tear Suturing after Vaginal Delivery: A Comparative Study - Rahmawati, Rahmawati; Lotisna, David; Abdullah, Nusratuddin; Chalid, Maisuri T; Tessy, Telly (Indonesian Socety of Obstetrics and Gynecology, 2018)
Abstract Objective : To compare the effectiveness of topically applied lidocaine-prilocaine cream with lidocaine-HCl injection in the reduction of pain during second degree of perineal tear suturing after vaginal delivery. Methods : One hundred and twenty-four of women with second degree of perineal tear after vaginal delivery were enrolled in this randomized clinical trial. Women were assigned randomly to have either application of lidocaine-prilocaine cream (n=62) or local injection of lidocaine-HCl (n=62) for anesthetic during perineal suturing. Pain measured with viasual analog scale (VAS) for the first 5 minutes during the perineal suturing. Statistical analysis was performed by comparative analytic numerical unpaired with independent t test between the two groups and significance was assessed at p<0.05. Data were presented as mean ± standard deviation (SD). Results : There was no significantly different of pain score between lidocaine-prilocaine cream and lidocaine-HCl injection group (5.66±1.07 vs 5.56±1.5; p=0.473). Conclusion : Application of lidocaine-prolicaine cream as effective as injection of lidocaine for reducing pain during second degree of perineal tear suturing after vaginal delivery. Keywords : Lidocaine-prilocaine cream, lidocaine-HCl injection, pain, perineal suturing, vaginal delivery     Abstrak Tujuan: Untuk membandingkan efektivitas antara lidokain-prilokain topikal dan lidokain-HCl injeksi dalam mengurangi nyeri selama penjahitan luka perineum tingkat dua setelah persalinan normal. Metode: Seratus dua puluh empat perempuan dengan robekan perineum tingkat dua postpartum pervaginam mengikuti uji coba klinis secara acak ini. Enam puluh dua perempuan (n=62) menggunakan lidokain-prilokain topikal dan 62 perempuan lainnya (n=62) menggunakan injeksi lokal lidokain-HCl untuk anestesi selama penjahitan perineum. Nyeri diukur dengan visual analog scale (VAS) untuk 5 menit pertama selama penjahitan perineum. Analisis statistik dilakukan dengan uji numerik komparatif tidak berpasangan dengan uji t independen antara kedua kelompok dengan tingkat kemaknaan p<0,05. Data disajikan sebagai rerata ± standar deviasi (SD). Hasil: Tidak terdapat perbedaan signifikan skor nyeri antara kelompok  lidokain-prilokain topikal dan kelompok injeksi lidokain-HCl (5,66 ± 1,07 vs 5,56 ± 1,5; p = 0,473). Kesimpulan : Efektifitas lidokain-prolikain topikal untuk mengurangi nyeri sama dengan injeksi lidokain-HCl selama penjahitan robekan perineum tingkat dua postpartum pervaginam. Kata kunci : Lidokain-prolikain topical, lidokain-HCl injeksi, nyeri, penjahitan perineum, persalinan normal